HABITAT HEALTH OF ILOILO RIVER - INSIGHTS FROM A STUDY ON BENTHIC COMMUNITY STRUCTURE - Palla, Rocille Quilantang; Campos, Wilfredo Lopez; Campos, Annabelle del Norte- (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2013)
In west central Philippines, the monitoring of aquatic systems traditionally focused on dissolved oxygen values and biological oxygen demand, e.g. monitoring by the Environmental Monitoring Bureau around Panay Island. However, single or two factors are considered to be insufficient to assess habitat health precisely. In this paper, we investigated a benthic community and xamined their implications to habitat health of the Iloilo River. According to a prior benthic survey, warning signs pertaining to biotic, abiotic and community factors have been detected. The disturbed onditions in Iloilo River can be attributed to 3 factors; 1) its inherent topography, where bends serve as sinks for materials; 2) the lack of vigorous water exchange that promotes deposition and hinders complete flushing; and 3) the manner of utilization of the river by the local people. We thus concluded that: 1) monitoring for water parameters only is not enough to get a clear picture of habitat health; and 2) proposed that biotic components should be included for monitoring aquatic system.